'Our society lacks consistently defined attitudes towards the black bear': The History of Black Bear Hunting and Management in Ontario, 1912-1987 - Commito, Michael (My University, 2015)
What kind of animal was a black bear? Were black bears primarily pests, pets, furbearers or game animals? Farmers, conservationists, tourists, trappers, and hunters in early twentieth-century Ontario could not agree. Even as the century progressed, ideas about bears remained twisted and there was often very little consensus about what the animal represented. These varying perceptions complicated the efforts of the provincial Department of Game and Fisheries and its successor agencies, the Department of Lands and Forests and the Ministry of Natural Resources, to develop coherent bear management policies. Perceptions about black bears often conflicted and competed with one another and at no one time did they have a single meaning in Ontario. The image of Ontario’s black bears has been continuously negotiated as human values, attitudes, and policies have changed over time. As a result, because of various and often competing perspectives, the province’s bear management program, for most of the twentieth century, was very loose and haphazard because the animal had never been uniformly defined or valued. Examining the history of these ambiguous viewpoints towards the black bear in Ontario provides us with a snapshot of how culture intersects with our natural resources and may pose challenges for management.
Keywords: environmental history; wildlife management; Ontario history; Canadian history; black bears